Persepsi Mahasiswa Terhadap Kode Etik Penggunaan AI dalam Pembelajaran Digital - Shifa Fauziah; Herlina Ananda; Liliana Swastina (Majalah Ilmiah METHODA, 2026)
The rapid adoption of generative artificial intelligence (AI) in higher education has changed how university students learn, write, and complete academic tasks, while simultaneously raising new ethical questions that existing codes of academic conduct have not fully anticipated. This article examines student perceptions of the ethics and codes of conduct surrounding AI use in digital learning through a structured literature review of credible academic sources published between 2021 and 2026. The review indicates that students generally hold positive attitudes toward AI as a learning aid, yet they also express concern over academic integrity, algorithmic bias, and limited transparency. A persistent gap is found between the pace of AI adoption and students' awareness of formal institutional guidelines or codes of ethics. The article concludes that strengthening ethical AI use among students requires a combination of AI literacy education, explicit institutional policy, authentic assessment design, and continuous socialization across academic communities.